Rational Design of an Activatable Reporter for Quantitative Imaging of RNA Aberrant Splicing In Vivo - Xie, Jinrong; Zheng, Haifeng; Chen, Si; Shi, Xiaorui; Mao, Wenjie; Wang, Fu (Molecular therapy. Methods & clinical development, 2020)
Pre-mRNA splicing, the process of removing introns from pre-mRNA and the arrangement of exons to produce mature transcripts, is a crucial step in the expression of most eukaryote genes. However, the splicing kinetics remain poorly characterized in living cells, mainly because current methods cannot provide the dynamic information of splicing events. Here, we developed a genetically encoded bioluminescence reporter for real-time imaging of the pre-mRNA splicing process in living subjects. We showed that the bioluminescence reporter is able to visualize the pre-mRNA aberrant splicing process in living cells in a dose- and time-dependent manner. Moreover, this reporter could provide quantitative and longitudinal information of splicing activity in response to exogenous splicing inhibitors in living animals. Our data suggest that this activatable reporter could serve as a promising tool for the high-throughput screening of splicing modulators, which would facilitate the drug development for human diseases caused by the abnormal splicing of mRNA. [Display omitted] In this study, Dr. Fu Wang and colleagues developed a genetically encoded bioluminescence reporter for real-time imaging of the pre-mRNA splicing process in living subjects, indicating a promising tool for the high-throughput screening of splicing modulators.